Factor Structure and Measurement Invariance of the Patient Health Questionnaire-4 Among the Chilean Population - Moreno-Herrera, F (Public Library of Science, 2024)
Background The PHQ-4 is an ultrabrief screening test for depression and anxiety symptoms. The psychometric properties of this test among the population in Chile are unknown. This study was aimed to determine the factor structure of the PHQ-4 in the adult population in Chile, and to assess its measurement invariance across different groups. Methods The study considered a nationally representative sample of 10921 people aged 18 and above, in Chile in 2021. Exploratory and confirmatory factor analysis were conducted, and configural, metric, scalar, and strict measurement invariance were assessed. Results The two-factor structure of the PHQ-4 supported the two underlying constructs of depression and anxiety. This model explained 67% of the variance and had excellent fit (CFI: 0.9999; TLI: 0.9994; RMSEA: 0.0107; SRMR: 0.0022). Strict measurement invariance held across gender, age, area of residence, household income quintile, immigrant or host population, and indigenous or non-indigenous population (ΔCFI<0.01). Conclusion The PHQ-4 can be used to assess depressive and anxiety symptoms in population studies, and as a screening test for depression and anxiety in public mental health programs in Chile. © 2024 Moreno, Moreno. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.